Nontuberculous mycobacterial infection mimicking gynecologic malignancy in a woman living with HIV - Tsung-Yu Tsai; Yi-Jou Tai; Aristine Cheng; Tai-Fen Lee; Szu-Ting Huang; Kuan-Yin Lin; Chien-Ching Hung (International Journal of Infectious Diseases, 2023)
The weakened immune system in people living with HIV (PLWH) can lead to infectious diseases occurring more aggressively and mimicking the clinical manifestations of malignancies. Mycobacterium sherrisii, a slow-growing nontuberculous mycobacterium, may cause opportunistic infections among PLWH. We present a case of a 41-year-old woman who initially presented with fever, vaginal spotting, and a bulky pelvic mass, raising suspicion of uterine malignancy. Following a surgical resection, she was pathologically diagnosed with leiomyoma and endometriosis. However, during an event of needlestick injury, she was unexpectedly found to be HIV-infected and the CD4 count was 157 cells/µL at diagnosis, which prompted a diagnostic work-up for opportunistic infections. The diagnosis of disseminated M. sherrisii infection was confirmed through cultures and special staining of specimens obtained from the pelvic tumor and blood. Subsequently, she was treated with a combination of ethambutol, azithromycin, and levofloxacin. Two months after treatment, abdominal and pelvic computed tomography revealed no evidence of recurrent tumor or abscess formation. Given the frequent association of pelvic masses with gynecologic malignancies in women living with HIV, it can be challenging to differentiate between a cancerous lesion and an infectious process, emphasizing the need for meticulous investigations to minimize the potential for misdiagnosis.